The Concept Of Faith and Moral In Badiuzzaman Said Nursi’s Philosophy - Sri Indah Mulyantiningsih; Anita Puji Astutik (Transformatif, 2022)
Said Nursi wants to actualize the progress in Islam which is part of the nation and the manifestation of the Shari’a rules. The idea of faith and morality concept initiated by Said Nursi shows that other things from the faith not only about the theological field, but also the sociological field, especially in morals. The method used in conducting this research is Library Research with Character Study approach supported by socio-historical analysis. The supporting data are collected from the library through books or literacy works, as well as several documents that used as the main data in this research. The concept of faith according to Said Nursi is tashdiq bil qolbi waikraru billisan ‘amalu bil arkan and the concept of morality shown by Said Nursi is not only an attitude of nationalism towards the country, but also maintaining the honor and glory of Islamic nationalism and loving the motherland and religion at the same time.